Coping styles in patients with haematological cancer in a Malaysian hospital. - Awang , Hamidin; Priscilla , D.; M.Z., Azhar; K.O.N., Noorjan; M.S. , Salmiah; K., Bahariah (Hong Kong Academy of Medicine Press, 2011)

(untitled)
OBJECTIVE: To assess coping styles of haematological cancer patients and investigate factors (major depressive disorders, socio-demographic profiles and clinical factors) that influence them. METHODS:This was a cross-sectional study conducted at the Ampang Hospital in Kuala Lumpur, Malaysia, which is a tertiary referral centre for haematological diseases. In all, 105 patients with haematological cancer were assessed using the Brief COPE questionnaire to examine the coping styles of patients, and the Mini-International Neuropsychiatric Interview to assess major depressive disorder. RESULTS:The response rate was 83%. The coping strategies used by haematological cancer patients in descending order of frequency were: behavioural disengagement, active coping, denial, venting, self-distraction, substance use, acceptance, humour, use of emotional support, use of instrumental support, religion, positive reframing, planning, and self-blame. The coping styles were found to be associated with major depressive disorder, socio-demographic profiles, and clinical factors. Self-distraction and positive reframing coping styles were significant predictors and related to major depressive disorder. CONCLUSION:The early identification of poor coping styles in cancer patients is important, in order to enhance their survival and prevent relapses.